Climate change in Lebanon: Higher-order regional impacts from agriculture - Eduardo A. Haddad; Nadim Farajalla; Marina Camargo; Ricardo L. Lopes; Flavio V. Vieira (REGION, 2014)
In this paper, we analyze the susceptibility of agricultural outputs to future climate change in Lebanon, and the extent to which it propagates to the economic system as a whole. We use a methodological framework in which physical and economic models are integrated for assessing the higher-order economic impacts of projected climate changes. By using this integrated modeling approach, we are able to quantify the broader economic impacts in the country by considering not only the temporal dimension but also the regional disaggregation of the results. Our estimates suggest that there are high potential costs and risks associated with a burden to the poorer and more vulnerable regions of the country.
Keywords: 330; Climate change; Economic Impacts; Agriculture; Integrated Modeling; Interregional CGE analysis; Regional Science; Regional Economics; Lebanon; Scenario 2010-2030; Governorates in Lebanon